A Post-War Paradox of Informality in South Lebanon: Rebuilding Houses or Destroying Legitimacy - Mollica, Marcello (Studies of Transition States and Societies, 2014)
Recent multiethnic Lebanese history has been characterised by a high degree of tension between sectarian groups and the state. In a number of cases, minority groups’ resistance to localised majority groups developed into a manifest attempt to limit the action of the central authority by embracing alternative loyalties, both transnational and interreligious. Makdisi (2000) argues that in a multiconfessional Lebanon the old-fashioned idea of longstanding violence between competing sects is unsustainable. However, political microanalysis based on empirical material collected in South Lebanon during and after the 2006 war shows that in situations where state and ethno-religious groups fail to establish a dialogue, tension leads citizens to view the state as alien and other groups as enemies.With reference to Christian minority group responses, this paper looks at the ways Hizbullah post-conflict strategies of reconstruction have been legitimated. Considering the Weberian notion of the state’s sole power and Prato’s (2000) analysis of citizen loyalties to the state as a welfare provider, and reassessing this notion with empirical data collected in conflictual loci, this paper examines the rise of a religion-driven movement in a scenario marked by dramatic economic transformation. The analysis suggests that group denial of the state’s role is most evident at a local level, where sectarian attitudes (e.g. concerning land or property issues) take precedence over nationally based loyalties and where this denial is the only perceptible means of survival for both the individual and his or her group.